Instagram Management Strategy as a Public Information Media by The Government of Bogor City During Covid-19 Pandemic - Ade Putri Lestari; Muhammad Al Assad Rohimakumullah (Kanal: Jurnal Ilmu Komunikasi, 2022)
The Covid-19 pandemic has encouraged the Bogor City Government to adapt to all forms of new habits in its public relations activities, one of which is by using Instagram as a public information medium to disseminate important information to the broader community. The purpose of this research was to determine the Instagram management strategy used by the Bogor City Government during the Covid-19 pandemic. This research uses a case study qualitative approach. The informant determination technique used is purposive sampling. The researcher chose informants who came from the internal Diskominfo Kota Bogor because they were considered according to the required criteria, namely being responsible for managing Instagram for the Bogor City Government. This research also uses data validity techniques, namely triangulation of data sources. The results of this research indicate that the Bogor City Government implements a public relations strategy process, including Fact-finding which is the way managers obtain materials for Instagram content, Planning which is the process of formulating and determining strategies and the objectives of Instagram management, Communication which is the use of creative content as a way of to implement a predetermined Instagram management strategy, and Evaluation which is conducting social media monitoring to evaluate the Bogor City Government Instagram management.